2019
DOI: 10.1371/journal.pone.0219517
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing responsive and refractory orthotopic mouse models of hepatocellular carcinoma in cancer immunotherapy

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and has a high mortality rate due to limited treatment options. Hence, the response of HCC to different cancer immunotherapies is being intensively investigated in clinical trials. Immune checkpoint blockers (ICB) show promising results, albeit for a minority of HCC patients. Mouse models are commonly used to evaluate new therapeutic agents or regimens. However, to make clinical translation more successful, better characterized preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Thus, LipC6 in combination with αCTLA‐4 Ab can be quickly translated into the clinical application for HCC treatment. Hage et al reported that combined treatment with αPD1 Ab and αCTLA4 Ab generated the response in the transplanted Hep‐55 model, but not in the transgenic iAST model, suggesting combined blockade of PD1 and CTLA4 has a selective effect in suppressing tumor growth 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, LipC6 in combination with αCTLA‐4 Ab can be quickly translated into the clinical application for HCC treatment. Hage et al reported that combined treatment with αPD1 Ab and αCTLA4 Ab generated the response in the transplanted Hep‐55 model, but not in the transgenic iAST model, suggesting combined blockade of PD1 and CTLA4 has a selective effect in suppressing tumor growth 41 …”
Section: Discussionmentioning
confidence: 99%
“…Hage et al reported that combined treatment with αPD1 Ab and αCTLA4 Ab generated the response in the transplanted Hep-55 model, but not in the transgenic iAST model, suggesting combined blockade of PD1 and CTLA4 has a selective effect in suppressing tumor growth. 41 We are going to further test the therapeutic efficacy of LipC6 in combination with both αCTLA4 and αPD1 Abs in HCC treatment.…”
Section: Molecular Events In Association With T Cell Activation Induc...mentioning
confidence: 99%
“…In contrast, orthotopic models more accurately reflect the natural TME of the organ in which tumorigenesis proceeds. Hage et al characterized one such syngeneic orthotopic model involving hepatic implantation of Hep-55.1c cells (42).…”
Section: Syngeneic Implantation Modelsmentioning
confidence: 99%
“…μCT is also used in combination with single photon emission computed tomography (SPECT) and positron emission tomography (PET) to provide anatomical information. However, standalone μCT is also widely used due to its fast acquisition time, high spatial resolution resulting in accurate anatomical information, relatively simple image analysis, and diverse application possibilities ( 1 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Now-a-days, it is the prevailing liver cancer with increasing incidence ( 4 ). Multiple HCC mouse models are used preclinically to assess the treatment response of new drugs ( 1 ). For example, Hage et al ( 1 ) characterized two HCC models, investigated their response to immune checkpoint blockers (anti-PD-1and anti-CTLA-4), and determined the orthotopic tumor growth by in vivo μCT imaging.…”
Section: Introductionmentioning
confidence: 99%